HUBUNGAN SELF CARE ACTIVITIES TERHADAP KADAR GLUKOSA DARAH PUASA PASIEN DIABETES MELLITUS (DM) TIPE II DI RSUD KELET PROVINSI JAWA TENGAH - Venti Agustina; Nining Puji Astuti; Hana Febi Naranti (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2022)
Background: Diabetes mellitus is a chronic disease that requires a lifelong treatment to maintain the quality of life of the patient. Treatment that can be done by Type II DM patients is self care for the aim of blood sugar control. Research Purposes: Describe the relationship between self-care activities and fasting blood glucose levels in Type II DM patients at Kelet Regional Hospital, Central Java Province. Method: This research uses an analytic descriptive method with a cross sectional approach at Kelet Regional Hospital, Central Java Province. Sampling techniques using purposive sampling techniques and obtained the number of research samples 120 respondents based on inclusion and exclusion criteria. The research instrument uses the DSMQ (Diabetes Self-Management Questionnaire) questionnaire and the measurement of fasting blood glucose. Data analysis was carried out by univariate and bivariate analysis which was then analyzed using the Spearman-Rank test. Results: The results showed that 88.3% of respondents had enough self care activities with 96.6% of respondents had GDP results > 100 mg/dl. In addition, all components of self care activities are in a sufficient category with 85%blood sugar monitor details, eating patterns 74.2%, physical activity 64.2%, treatment 89.2%. The Spearman-Rank test results showed the relationship between self care activities and fasting blood glucose with the value of P=0.036. The self care component associated with fasting blood glucose is the regulation of diet (P=0.028) and physical activity (P=0.036). Conclusion: There is a relationship between self-care activities and fasting blood glucose levels in type II DM patients at Kelet Hospital, Central Java Province. The self care component associated with GDP is the arrangement of diet and physical activity. Keyword: DM type II, DSMQ, GDP, self-care